2023
DOI: 10.1111/cbdd.14324
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine attenuates myocardial ischemia–reperfusion injury in hyperlipidemic rats by inhibiting inflammation, oxidative stress and NF‐κB

Weiwei Gao,
Liang Du,
Nan Li
et al.

Abstract: The present study was conducted to determine the protective effect of Dexmedetomidine (DEX) in myocardial ischemia–reperfusion injury in hyperlipidemic rats. Towards this, the effect of DEX was first evaluated on the infarct size and the histopathology of cardiac tissues using TTC and H and E staining, and it was found that DEX significantly improved the infarct size and architecture of the myocardial tissues following the I/R injury. DEX also showed significant improvement in various examined hemodynamic para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…28 Moreover, dexmedetomidine showed beneficial effects in ischaemia-reperfusion experimental models, and several studies have shown significant clinical effects of dexmedetomidine after cardiac surgery, making this drug of high interest in this field. [29][30][31] Other drugs such as esmolol or magnesium have been used as alternatives to opioids. Nevertheless, we think that their use during cardiac surgery may favour circulatory failure and may interfere with CPB management through interference with cardioplegia drugs, delayed weaning from CPB, etc, suggesting the combination of lidocaine/dexmedetomidine as our first choice.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…28 Moreover, dexmedetomidine showed beneficial effects in ischaemia-reperfusion experimental models, and several studies have shown significant clinical effects of dexmedetomidine after cardiac surgery, making this drug of high interest in this field. [29][30][31] Other drugs such as esmolol or magnesium have been used as alternatives to opioids. Nevertheless, we think that their use during cardiac surgery may favour circulatory failure and may interfere with CPB management through interference with cardioplegia drugs, delayed weaning from CPB, etc, suggesting the combination of lidocaine/dexmedetomidine as our first choice.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%